CP-176 Innovation at any cost? management of innovative therapies in a health facility. (25th February 2017) - Sabatier, M; Jurado, C; Vert, C; Fiore-Faye, C di; Bellon, B; Eyvrard, F
Abstract : Background: Access to innovative therapies has been regulated since 1994 by the introduction of the first temporary authorisation for use (TAU) for drugs without marketing authorisation (MA) in patients with acquired immunodeficiency syndrome. This provision was compassionate and free. Nowadays, the process still exists but has evolved, particularly regarding treatment costs imposed by pharmaceutical companies without any competent authorities' regulation, impacting on national health expenditure objectives. Purpose: The aim of this study was to design and validate the organisation of TAU drug administration reports in hospital to ensure their specific refund to the hospital Material and methods: The scope was drugs under TAU, administered at a health facility over 18 months. Financial issues were assessed by (i) annual balance 'E/I' (€): expenses (from financial management software: FMS) over incomes (from national allocated budgets), (ii) lack of completeness (E/I corrected ratio: we removed from the annual expenses those without income expected) and (iii) evolution of expenditures for the next year. Finally, process escape was evaluated by refund modalities of drugs recently out of the TAU process. Results: The organisation relies on four principles: regulatory monitoring of TAU status change to MA, hospital data pharmaceutical validation, exhaustive drug administration statements to competent authorities (regulatory framework governing TAU requires refunds related to administration declarations) and refund tracking. In 2015, we identified a balance E/I=3 million/2.7 million; 6% lack of completeness was attributable to errors in FMS, administration traceability or newest TAU drugs late integration in the competent authority's refund database. The first semester of 2016 showed evolution of these parameters: E/I=5.7 million/5.6 million, 1% lack of completeness, associated with market share increase of oncologic immunotherapy (+48%). After the TAU period, some drugs no longer benefited from a specific refund and then relied on hospital budgets (€200 000 in 2016). Conclusion: Although interest in treating patients with these drugs is validated, issues arise when specific refunds in the TAU period are no longer financed post-market. Then the TAU strategy tends to lose its original virtue of providing innovating molecules without additional cost for hospitals. Without an early cost control strategy (since TAU initiation), high prices for innovative and monopolistic medicines could jeopardise healthcare financing systems. No conflict of interest